Leveraging new media for the branding of pinge tourism village - Widianti, Mira Adita; Sepriandana, Ridhwan (Privietlab, 2025)
New media is common in the digital era. New media is media that is connected to the internet, allowing it to be accessed by the wider community anywhere and anytime. Some of the new media familiar to mass media are social media and websites. The use of new media can be utilized if people want to know about certain brands, products or services. Through new media, users can actively participate openly and interactively to convey, receive, and discuss new ideas as a basis for making better business decisions. The use of new media can be applied in forming a Tourism Village brand. This research focuses on how to use new media to establish the brand of Pinge Tourism Village, Tabanan Regency, Bali. Data were collected from interviews with the management of the Pinge Tourism Village, analysis of social media and the Pinge Tourism Village website, and direct observation at the research location. The method used is a qualitative research approach that explores how the Pinge Tourism Village brand was formed through new media. The results show that Pinge Tourism Village utilizes social media using the main features of Facebook and is in accordance with the branding concept. They also use websites for branding.